Study on Reproductive Biology of some Indigenous Cat Fish - Yassung, Koj; Minare, Anubhuti; Vyas, Vipin (AG Volumes, 2025)
The present study investigates the reproductive biology of selected indigenous catfish species Mystus tengara, Mystus vittatus, Clarias batrachus, and Heteropneustes fossilis collected from local markets in Bhopal, Madhya Pradesh, over a five-month period from August to December 2023. The research was conducted at the Department of Zoology and Applied Aquaculture, Barkatullah University, Bhopal. Monthly samples were analyzed to assess variations in total length, body weight, ovary length, ovary weight, Gonado-somatic Index (GSI), fecundity, and ova diameter to better understand the reproductive cycles and spawning seasons of these species. The maturity stages of the gonads were determined through macroscopic examination, and the GSI was calculated using the standard formula to track gonadal development. Fecundity was estimated gravimetrically by counting ova from different regions of the ovary, while ova diameter was measured using an ocular micrometer. The findings revealed distinct seasonal patterns in reproductive parameters among the studied species. Mystus tengara showed peak reproductive indicators in August, with maximum length (15 cm), weight (40 g), and ovary development. In Mystus vittatus, peak reproductive activity occurred in September, whereas in Clarias batrachus, reproductive maturity was most pronounced in October. Heteropneustes fossilis exhibited its highest GSI, ovary length, and weight in September, declining sharply by December. These variations in reproductive traits across species and months highlight their specific breeding seasons and reproductive strategies. The results of this study are significant for formulating conservation strategies and improving captive breeding programs for indigenous catfish in central India.